Análise da mediação e da conciliação, como instrumentos de garantia de acesso à justiça, e a política educacional dos cursos de direito na comarca de Sobral - Azevedo, Hienes Martins (2024)
The Brazilian Judiciary faces a significant challenge due to the growing number of lawsuits and the resulting overload of the system, compromising the quality and efficiency of the provision of justice. This high number of lawsuits triggered the need to adopt public policies that could decongest the Judiciary, promoting faster and more effective conflict resolution. Thus, consensual forms of conflict resolution have received greater encouragement over the last few decades, especially mediation and conciliation, which have been highlighted since Resolution No. 125, published on November 29, 2010, by the National Council of Justice, which regulated the implementation of the Policy for Adequate Treatment of Conflict Resolution. As a result, this research aims to understand to what extent these conflict resolution mechanisms have effectively contributed to access to justice, specifically in the context of the Judicial Center for Conflict Resolution and Citizenship of the District of Sobral, located in the state of Ceará. The purpose of this study is to examine the statistical scenario of pre-trial and trial demands in the District of Sobral, verifying the impact of mediation and conciliation in containing lawsuits filed in court, comparing the local scenario with state and national data, through a documentary analysis of statistics provided by the Permanent Center for Consensual Methods of Conflict Resolution (NUPEMEC), statistical reports made available by the Court of Justice of the State of Ceará (TJCE) and the annual report prepared by the National Council of Justice (CNJ). On the other hand, it was found necessary to also analyze the contribution of educational policy in undergraduate law courses, as tools to encourage the use of these consensual methods of conflict resolution by future legal professionals. The methodology adopted is applied, qualitative and exploratory research, carried out through a bibliographic review of national and international sources to support the empirical research conducted at CEJUSC, with data collection through documentary analysis in reports from the TJCE and the CNJ itself. The post-pandemic period (2022-2023) was selected as the time frame. The expectation is that the results of this research will contribute to a broader reflection on the importance of mediation and conciliation as effective mechanisms for access to justice in the District of Sobral. In addition, it is expected to provide subsidies to contribute to the training of graduates of law courses at the Vale do Acaraú State University, in order to develop skills aimed at a culture based on dialogue and the use of consensual forms of conflict.